TEACHING ADJECTIVES AT PRIMARY SCHOOLS IN UZBEKISTAN - No’monova M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores the challenges faced by primary school educators in Uzbekistan when teaching adjectives. The study aims to shed light on the specific obstacles that teachers encounter and suggests potential strategies to address these difficulties. By understanding the unique linguistic and cultural context of Uzbekistan, educators can develop more effective teaching methods for enhancing learners' grasp of adjectives.